2020
DOI: 10.1021/acsami.0c09653
|View full text |Cite
|
Sign up to set email alerts
|

Fully Elastomeric Fingerprint-Shaped Electronic Skin Based on Tunable Patterned Graphene/Silver Nanocomposites

Abstract: Multifunctional electronic skins (e-skins), which mimic the somatosensory system of human skin, have been widely employed in wearable devices for intelligent robotics, prosthetics, and human health monitoring. Relatively low sensitivity and severe mutual interferences of multiple stimuli detection have limited the applications of the existing e-skins. To address these challenges, inspired by the physical texture of the natural fingerprint, a novel fully elastomeric e-skin is developed herein for highly sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
(95 reference statements)
0
46
0
Order By: Relevance
“…Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals. [45,46] The electrical types of wearable sensors can be classified into three groups: chemiresistive, conductometric, and impedimetric.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals. [45,46] The electrical types of wearable sensors can be classified into three groups: chemiresistive, conductometric, and impedimetric.…”
Section: Resultsmentioning
confidence: 99%
“…The GO mesotubes behaved like a soft gel with a Young's modulus of 974 Pa and were robust to 10 5 cycles of bending tests, rendering them promising candidates as wet sensors for soft robotics [26][27][28][29] and electronic skins. [30][31][32][33] As a proof of concept, we demonstrated that a single GO mesotube can be used as a wet-conditioned sensor for monitoring mechanical vibration and human artery pulse pressure. However, the possible applications of GO mesotubes are not limited to these examples.…”
Section: Introductionmentioning
confidence: 99%
“…A more straightforward and efficient method is to propose a novel structure design that can help separate the pressure and temperature stimuli, so the coupling interference of the e-skin can be remarkably reduced. Moreover, current works of e-skins have mainly involved singleor few-point detection and some have reported large-scale rectangular-shaped arrays, [18,32,35,43,44] which are difficult to be conformably integrated with the human or robotic hand. The dense but nonuniform distribution of the mechanoreceptors in human hand is a good inspiration for the distribution design of sensor arrays, and researchers have made efforts in imitating the mechanoreceptors to fabricate tactile sensor arrays with high density.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible tactile sensors have been developed based on various transduction mechanisms, such as capacitive [21], piezoresistive [22,23], piezoelectric [24], and triboelectric effects [25]. Among them, the piezoresistive type has exhibited intensive potentials due to their excellent flexibility, relatively high sensitivity, and broad measuring range [26,27].…”
Section: Introductionmentioning
confidence: 99%